Epidemiological Pattern of Cutaneous Leishmaniasis in Al-Khums City, Libya: A Descriptive Study (2024–2025) (مجلة البحوث الأكاديمية, 2025)
Cutaneous leishmaniasis (CL) is a vector-born parasitic diseaseendemic inmany Mediterranean and Middle Eastern regions. This study describes theepidemiological characteristics of CL in Al-Khums City, Libya, between 2024and 2025. Data from 802 confirmed cases were analyzed according to gender,age, region, and monthly distribution. Males accounted for 61.7% of cases.The most affected age group was 45–54 years (16.2%). Seasonal variationwasmarked, with case peaks in December 163 ( 20.3%)and January  209 (26.0%)  . Pearsoncorrelation revealed a strong inverse relationship between monthprogressionand CL incidence (r = −0.96, p = 0.001). Al-Amamera, Al-Daawon, and Al-Ma‘qula were identified as major hotspots. Findings highlight significantseasonal and spatial clustering of CL and underscore the need for targetedwinter-season vector control.